Pengaruh Logoterapi untuk Meningkatkan Motivasi Belajar Mahasiswa - Yasin Syarif Hidayatulloh; Fildzah Malahati (VISA: Journal of Vision and Ideas, 2026)
This study aims to examine the effectiveness of logotherapy in enhancing students’ learning motivation. The research employed a quantitative experimental method with a pretest-posttest design. The subjects consisted of 10 first-year students at Universitas Aisyiyah Yogyakarta, selected using purposive sampling. Logotherapy sessions were conducted, and learning motivation was measured before and after the intervention. Data were analyzed using the Wilcoxon test. The results showed a significance value of p = 0.705 (p > 0.05), indicating no significant difference in students’ learning motivation scores before and after the intervention. These findings suggest that short-duration and limited-intensity logotherapy is not sufficient to produce a meaningful impact on students’ learning motivation. Other contributing factors may include limited intervention sessions, small sample size, and external academic conditions. The study recommends that logotherapy should be conducted over a longer period, with more sessions, and combined with practical learning strategies to achieve more effective outcomes.